Care Workers for Change: Multi-dimensional union organising in a hostile environment. (July 2019) - Nelson, Kevan
Abstract : This article is based on UNISON's experience of organising workers in the adult social care sector in the northwest of England. The article draws on the Marxist theoretical approach that has been developed by John Kelly and the work on organising that has been developed by Jane McAlevey to identify some strategic choices that trade unions encounter in general. The specific case of UNISON North West's Care Workers for Change campaign is then discussed in relation to these choices. In confronting a hostile environment for organising, we regard our approach in practice as multi-dimensional, as we have drawn on a variety of ideas and tactics, including those of Kelly and McAlevey, and have tailored our approach to the specific conditions in the care sector.